Konsep Pendidikan Karakter di Paguyuban Penghayat Kepercayaan Hangudi Bawana Tata Lahir Batin Yogyakarta: Perspektif Pendidikan Islam - Ilma Afidah Nur Diana (Nusantara: Jurnal Pendidikan Indonesia, 2022)
The Hangudi Bawana Tata Lahir Batin Association has consistently nurtured its character through several rituals and activities. However, this association often gets stigma and rejection because it is considered contrary to the character of Islam. Therefore, there is a need for research that describes the concept of Character Education in the Society in the Perspective of Islamic Education. This research is qualitative research. The subject of the research is the Chairperson, the administrator, and two people (members) in the Hangudi Bawana Tata Lahir Batin Association Yogyakarta. Data was collected by interview, observation, and documentation methods. The data analysis technique uses the Miles Huberman model, which consists of data reduction, data display, verification. The data validity technique uses triangulation of sources, methods, and time techniques. The results of the study show that there are three characters of Islamic perspective developed in the Paguyuban, namely: 1) Divine character. 2) Human Character. 3) Natural Character. In its application, all the characters developed are implemented into activities carried out by the Paguyuban. Regarding character habituation, this association has several methods used, including Qishah and Hiwar methods, uswah methods, refraction methods, promises and threats methods and ibrah and mau'idah methods.